Symptomatic preterm infants suffer from lung function deficits, regardless of bronchopulmonary dysplasia - Tuková, Jana; Koucký, Václav; Marková, Daniela; Koťátko, Petr; Hladíková, Marie; Šulc, Jan (Pediatric pulmonology, 2022)
BACKGROUND: The long-term respiratory consequences for children with bronchopulmonary dysplasia (BPD) are well known. However, there is little emphasis on monitoring preterm infants without BPD. Few studies have explored the lung function status of infants with the symptoms of chronic lung disease of prematurity (CLD). OBJECTIVE: To evaluate functional lung deficits in preterm infants with CLD, and to assess the perinatal determinants of diminished lung function. METHODS: In our cross-sectional study, 132 preterm infants with symptomatic CLD underwent infant pulmonary function testing (iPFT) at a median post-term age of 0.9 years. The iPFT included bodypletysmography, compliance measurement, tidal breath analysis, and rapid thoracoabdominal compression. The relationships between the respective z scores of the iPFT parameters and perinatal characteristics, postnatal treatment, and BPD status were investigated. RESULTS: Seventy-three patients (55.3%) were born before the 28th week of gestation, and 92 (69.7%) met the BPD criteria. Functional deficits were detected in 85.8%. The obstructive ventilatory pattern was more prevalent than restrictive (36.3 vs. 12.4%, p < 0.001). Infants with restriction had lower birth weight (BW) and required a longer duration of oxygenotherapy. In a univariate model, the lung function correlated with the duration of invasive mechanical ventilation, gestational week, and BW. In a general linear model, BPD status was not an additional determinant of the iPFT results. CONCLUSION: IPFT may reveal significant functional deficits in preterm infants with CLD even without BPD. The current symptoms and perinatal factors may be more important determinants of functional deficits than the BPD status itself.
Keywords: Cross-Sectional Studies; bronchopulmonální dysplazie; kojenec; prematurity; Gestational Age; Infant; průřezové studie; dítě; Child; gestační stáří; Infant, Newborn; Bronchopulmonary Dysplasia; airways obstruction; novorozenec; plíce; Humans; lung restriction; infant pulmonary function testing; Infant, Premature; Birth Weight; porodní hmotnost; chronic lung disease of prematurity; novorozenec nedonošený; Lung; lidé